The Molecular Mechanism by Which miR-129a-3p Targets the TLR4/NF-κB Signaling Pathway to Regulate Inflammatory Damage in 3D4/21 Cells Infected with Glaesserella parasuis - Zhongbo Guo; Yuanyuan Zhou; Na Li; Aobo Shen; Yongchao Jia; Ronglan Yin; Junjie Yang; Jing Yuan; Ronghuan Yin (Animals)
Glaesserella parasuis (G. parasuis) is the primary pathogen responsible for Glässer’s disease and poses a significant threat to the global pig industry. MicroRNAs are a class of short, endogenous, single-stranded noncoding RNAs that play crucial roles in inflammation, apoptosis, proliferation, differentiation, and invasion in various organisms. This study analyzed the characteristics of porcine alveolar macrophage (PAM) cells infected with G. parasuis through the knockdown and overexpression of ssc-miR-129a-3p. We constructed a cellular model with ssc-miR-129a-3p knockdown invaded by G. parasuis strain XX0306, screening 160 differentially expressed genes via high-throughput sequencing. GO enrichment analysis revealed that 376 GO entries were enriched. KEGG enrichment analysis found that mRNA target genes were enriched in 17 cell signaling pathways, including G protein-coupled components, PPAR, and other signaling pathways that can mediate inflammatory pathways. By examining the expression of relevant inflammatory factors and signaling pathways, we elucidated the molecular mechanisms through which ssc-miR-129a-3p targets the TLR4/NF-κB signaling pathway to regulate inflammatory injury. This study establishes a foundation for further research into the role of miRNA in the pathogenesis of Glässer disease and is highly significant for the prevention and control of bacterial diseases within the pig industry.